Parametric Modeling of the Human Mandible Lateral Body for the Shape Optimization of its Section in the Case of Bone Augmentation. (2015) - Mircea, Suciu; Razvan, Cazacu; Ionut, Grigoras Radu; Ioana, Bica Cristina
Abstract: The purpose of bone augmentation is linked to the creation of an ideal alveolar ridge that might support implant therapy or to assure perfect retention for a future complete or partial denture. The means of new bone structure formation and its resorption are both well-discussed themes in the last decade. For the edentulous alveolar ridge, it is important to have a better aspect both vertically and horizontally. The finite element analysis method use in the study of mandibular ridge bone loss has not been a main purpose in most dental studies. This paper is part of a more complex study regarding the FEA simulation of the mandible mechanical behavior in the case of mandibular crest augmentation with autogenous bone graft from the iliac crest. Its main aim is proposing a reduced parametric model for the lateral body of the mandible and asses its affinity to the complete model of the mandible. The results show this simplified model does indeed represent a reasonable approximation of the complete model and can be used for the optimization of the mandibular crest section shape. Further research should provide optimal values of the model parameters, an important aid for the clinicians performing bone augmentation.